Controls of soil and aggregate‐associated organic carbon variations following natural vegetation restoration on the Loess Plateau in China - Deng, Lei; Kim, Dong‐Gill; Peng, Changhui; Shangguan, Zhouping (Land degradation & development, 2018)
Natural vegetation restoration can enhance soil organic carbon (SOC) sequestration, but the mechanisms and control factors underlying SOC sequestration are still unknown. The objectives of the study are to quantify the temporal variation of soil and aggregate‐associated organic carbon (OC) and identify factors controlling the variation following natural vegetation restoration after farmland abandonment. We collected soils from sites having 5, 30, 60, 100, and 160 years of a natural vegetation restoration chronosequence after farmland abandonment in the Loess Plateau, China. The results showed that natural vegetation restoration increased macroaggregates (0.25–2 mm; 46.6% to 73.9%), SOC (2.27 to 9.81 g kg−1), and aggregate OC (7.33 to 36.98 g kg−1) in the top 20‐cm soil compared with abandoned farmland, and the increases mainly occurred in the early stage (<60 years). The increase of SOC was contributed by OC accumulated in macroaggregates (0.25–2 mm) rather than microaggregates (≤0.25 mm). Moreover, SOC sequestration in the topsoil (0–10 cm) was mainly determined by fine root biomass (FR), labile organic carbon (LOC), and microbial biomass carbon (MBC). And in the subsoil (10–20 cm), SOC sequestration was mainly determined by the proportion of macroaggregates. The results suggest that natural vegetation restoration increased SOC and aggregate OC, and FR, MBC, LOC, and the physical protection of aggregates played important roles in regulating SOC and aggregate OC.